CORRELATION BETWEEN CHANGES IN INTRA OCULAR PRESSURE AND MEAN ARTERIAL PRESSURE BEFORE AND AFTER DIALYSIS IN REGULAR DIALYSIS PATIENTS: Oral Presentation - Observational Study - Resident - Dewi, Anak Agung Ayu Surya Nirmala; Kusumadjaja, I Made Agus; Pemayun, Cokorda Istri Dewiyani (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesGlaucoma is an eye disorder characterized by glaucomatous optic neuropathy with a typical visualfield defect and increased intraocular pressure (IOP).The incidence of glaucoma in dialysis patient is8.18/10,000 person. The dialysis process may change the IOP and Mean Arterial Pressure (MAP)which may lead to glaucoma. The aims of this study are to determine whether there was a change inIOP and MAP and to determine the correlation between changes in IOP and MAP due to dialysis. MethodsThis is an observational study with cross sectional approach using stratified sampling method. Thesubjects were all regular dialysis patient at the Dialysis Unit in Sanglah Hospital period April-May2021 with total 63 people. The data taken are age,gender ,duration of dialysis, fasting blood sugar,urea and serum creatinine level before dialysis. Subjects were measured IOP and calculated MAPbefore and after dialysis. ResultsMean of age of this study was 47,03±12,06 years old and dominated by male. Paired T-Test showedno significant changes IOP after dialysis but there were significant decreased on systolic, diastolicand MAP. Pearson correlation showed no correlation between changes of IOP and MAP afterdialysis. Multivariate analysis shows significant correlation between changes of IOP with urea levelbefore dialysis. ConclusionIOP after dialysis was not increased in this study. Systolic, diastolic and MAP were decreased afterdialysis compared to before dialysis. There is no correlation between changes in IOP and MAP afterdialysis compared to before dialysis. Urea level before dialysis may be associated with increased IOPafter dialysis.